Clouds and plant ecophysiology: missing links for understanding climate change impacts - Hughes, Nicole M.; Sanchez, Adriana; Berry, Z. Carter; Smith, William K. (Frontiers in Forests and Global Change, 2024)
Observations and models indicate that human activity is altering cloud patterns on a global scale. Clouds impact incident visible and infrared radiation during both day and night, driving daily and seasonal variability in plant temperatures—a fundamental driver of all physiological processes. To understand the impacts of changing cloud patterns on essential plant-based processes such as carbon sequestration and food production, changes in local cloud regimes must be linked, via ecophysiology, with affected plant systems. This review provides a comprehensive treatment of cloud effects (apart from precipitation) on fundamental ecophysiological processes that serve as the basis of plant growth and reproduction. The radiative effects of major cloud types (cumulus, stratus, cirrus) are differentiated, as well as their relative impacts on plant microclimate and physiology. Cloud regimes of each climate zone (tropical, subtropical, temperate, polar) are superimposed over recent changes in cloud patterns and primary productivity in major ecosystems. The most robust trends in changing global patterns are as follows: (i) the tropical rain belt (comprised mostly of deep convective clouds) is narrowing, shifting latitudinally, and strengthening, corresponding with increased clouds and precipitation in some parts of the tropics, but decreases in others; (ii) subtropical dry zones are expanding poleward, corresponding with reductions in clouds (which are mostly altostratus and altocumulus at these latitudes); (iii) summer mid-latitude storm tracks are weakening and migrating poleward, and clouds in temperate regions are decreasing; and (iv) clouds over in the Arctic are increasing. Fewer low clouds in the tropics and reduced fog in many coastal regions have also been observed, although these trends can be partially attributed to local patterns of deforestation, urbanization, and/or reductions in aerosols associated with clean air initiatives. We conclude by highlighting gaps in the cloud-ecophysiology literature in order to encourage future research in this under-studied area.